ANALISIS MITIGASI PENANGGULANGAN BENCANA DI KABUPATEN OGAN KOMERING ULU PROVINSI SUMATERA SELATAN - EVA SUSANTI; Ikang Putra Anggara (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2020)
Natural disasters are a condition that we do not expect, therefore understanding the processes of a disaster and the factors that cause disasters is very important for the government and society. One of the disasters that is of concern to the government and the community is landslides that need to know the impact and how to overcome them. The alternative that can be taken is in the form of disaster management mitigation, this is able to reduce the sustainable risk of landslide vulnerability. This study aims to analyze and observe how disaster mitigation measures exist in Ogan Komering Ulu RegencyThis research is a descriptive type of research using a qualitative approach. The research subjects are individuals and / or groups who are expected to be able to tell what is known about something related to the phenomenon or case under study. The results of research and discussion, (Regional Disaster Management Agency)BPBD Ogan Komering Ulu as the agency in charge of disaster including landslides in carrying out mitigation stages such as mapping, inspection, investigation and socialization have not maximally carried out disaster mitigation. Disaster management measures are carried out by (Regional Disaster Management Agency)BPBD after a disaster occurs.